nab-Paclitaxel Plus Durvalumab in Patients With Previously Treated Advanced Stage Non-small Cell Lung Cancer (ABOUND.2L+) - Morgensztern, Daniel; Dols, Manuel Cobo; Ponce Aix, Santiago; Postmus, Pieter E.; Bennouna, Jaafar; Fischer, Jürgen R.; Juan-Vidal, Oscar; Stewart, David J.; Ardizzoni, Andrea; Bhore, Rafia; Wolfsteiner, Marianne; Reck, Martin; et al. (Frontiers in Oncology, 2021)
Background The standard therapy for advanced stage non-small cell lung cancer (NSCLC) with no actionable gene alterations is a platinum-based chemotherapy doublet and immune checkpoint blocker (ICB), either concurrent or sequentially, followed by docetaxel. However, more effective treatments are needed. We evaluated the nab-paclitaxel and durvalumab combination in patients with previously treated advanced stage NSCLC. Methods Patients with advanced stage NSCLC previously treated with one line of platinum-based doublet with or without an ICB, and no activating EGFR mutations or ALK translocations received nab-paclitaxel 100 mg/m2 (days 1 and 8) plus durvalumab 1125 mg (day 15) every 21 days. The primary endpoint was progression-free survival (PFS). Key secondary endpoints included overall survival (OS) and safety. Results Between February 2016 and December 2016, 79 patients were enrolled. The median age was 63 years. Most patients were males (68.4%), had non-squamous histology (69.6%), and no prior ICB treatment (88.6%). The median PFS was 4.5 months; median OS was 10.1 months. A post hoc analysis of survival by prior ICB treatment revealed a median PFS and OS of 4.4 and 9.9 months, respectively, in ICB-naive patients and 6.9 months and not estimable, respectively, in patients previously treated with ICB. The most common treatment-emergent adverse events were asthenia (46.2%) and diarrhea (34.6%); 4 treatment-related deaths (5.1%) occurred. Conclusions The nab-paclitaxel and durvalumab combination is feasible and demonstrated antitumor activity without new safety signals. Additional studies using taxanes and ICB in patients with previously treated NSCLC are warranted. ClinicalTrials.gov registration: NCT02250326 EudraCT number: 2014-001105-41